Kepatuhan Belanja Wajib Pendidikan dan Kesehatan: Studi Kasus 34 Provinsi di Indonesia - Klara Wonar; Boy Piter Nizu Kekry (Universitas Cenderawasih, 2022)
The purpose of this study is to reveal the level of compliance with compulsory education and health spending in 34 provinces in Indonesia. The method of analysis uses descriptive quantitative decision-making process through testing the assessment criteria. Consideration of the application of the method in the context of the effectiveness of the assessment of results, disclosure of facts with research objectives. The main finding of the study is that 34 provinces in Indonesia have not simultaneously complied with the laws and regulations regarding the allocation of 20 percent of compulsory education spending and 10 percent of health. It is realized that this research is limited in only one period of the fiscal year, besides that it only focuses on health and education. So it is hoped that further research can measure mandatory spending on infrastructure and villages nationally with time series data, the most important thing is whether mandatory spending compliance provides leverage on human development performance in Indonesia.